Amaranths for balanced nutrition - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The amaranth is often called a pseudocereal, and its grain has characteristics similar to those of the cereal grains. With protein levels of between 13-19%, amaranth is among the highest protein grains in the world. It has high levels of Iysine,...